(untitled) (Research, Society and Development, 2020)
The objective of this review was to carry out a scientific systematization on the logistics of soybean chain in Brazil, focusing on losses during harvest, storage, and transport of soy, to demonstrate the economic impacts of losses in the soybean chain. The survey of works related to the theme was conducted in the bases Scopus, SciELO, and in the CAPES portal. In the development of the review, 10 articles were used about the logistics of soybeans in Brazil, 22 studies related to losses in the pre-harvest and soybean harvest, 22 involving soybean transportation and storage losses. The organization of the Brazilian soybean chain is complex due to soybean expansion and the territorial extension of Brazil. The pre-harvest and harvest losses are well explained, but significant losses still occur due to lack of regulation in the harvesters, which can be solved through the training of the operators. Concerning losses during transport and storage, studies are needed to quantify quantitative losses, as these losses may be determinant for the rural entrepreneur’s profitability, as well as for the Brazilian competitiveness in the international market in terms of costs.